The Influence of Leadership and Work Culture on the Performance of Village Office Employees in Bunta District, Banggai Regency - Mangantjo, Rini; Indriani Ibrahim, Andi; Sipatu, Lindanur; Matalatta , Wisra; P. Adam, Rosida (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of leadership and work culture on employee performance in village offices in Bunta District, Banggai Regency. Using an associative quantitative design, data were collected through questionnaires from 49 employees selected by saturated sampling and analyzed using multiple linear regression. The findings show that leadership and work culture each have a positive and significant effect on employee performance and jointly exert a significant influence. These results indicate that improving leadership quality and fostering a constructive work culture can enhance employee performance and support more effective public service delivery at the village level. Keywords: Leadership, Work Environment, Teacher Performance